Experimental Estimates of the Student Attendance Production Function. (June 2021) - Tran, Long; Gershenson, Seth
Student attendance is both a critical input and intermediate output of the education production function. However, the malleable classroom-level determinants of student attendance are poorly understood. We estimate the causal effect of class size, class composition, and observable teacher qualifications on student attendance by leveraging the random classroom assignments made by Tennessee's Student/Teacher Achievement Ratio (STAR) Project class size experiment. A 10-student increase in class size increases the probability of being chronically absent by about 3 percentage points (21%). For Black students, random assignment to a Black teacher reduces the probability of chronic absence by 3.1 percentage points (26%). However, naive mediation analyses suggest that attendance is not a mechanism through which class size and same-race teachers improve student achievement.